Corrosion Layers on the Glass Surface of Na2O-K2O-CaO-ZrO2-SiO2 System. (2016) - Papučová, Iveta; Plško, Alfonz; Pagáčová, Jana
Abstract: Occurrence of corrosion layers on observed glass samples has been monitored by means of cyclic tests in distilled water. Occurred corrosion layers were characterized by their thickness and refractive index. Characteristics of corrosion layers were calculated from dependence of reflectance on wavelength in visible spectrum area for particular observed glass and corrosion times. Thickness of corrosion layers reached tens of nanometers. Refractive index of corrosion layer for all observed glass samples was lower than refractive index of original glass. Dependence of layer thickness on time was regarded as result of leaching kinetics for observed glass. Initial layer thickness growth is stabilized in the course of time for glass samples with ZrO2 content of 0.00 wt. % and 0.41 wt. %. There is considerable trend in layer thickness growth along with corrosion time for glass samples with ZrO2 content of 0.81 wt. %, 1.26 wt. % and 1.66 wt. %. From dependence of refractive index on time we have found out that refractive index of corrosion layers occurring on particular glass samples were changed. We have found difference in values of refractive index amongst particular glass samples and we have explained it via their different porosity.